Development of Rice Husk Reinforced Aluminium Chips Based Composite By Direct Recycling of Hot Press Forging - Chai, Chuan Yang; Shamsudin, Shazarel (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The research investigates about the rice husk reinforced aluminium chips by direct recycling. It is significant to study which will affect the physical and mechanical properties of composite. Due to increasing of natural wastes, rice husk is developed in an alternative method of recycling it as reinforcement for aluminium chips-based composite. Major purposes of this research are to investigate the physical property of directly recycled aluminium alloy AA6061 reinforced by rice husk via density test and simulate the effect of process parameters namely operation forging temperature, holding time, and weight percentage (wt%) of rice husk through DEFORM 3D software to reveal the optimum performance of the developed composite. The matrix composite used is recycled aluminium alloy AA6061 in chips with an average length of less than 4mm. The experiment is carried out by the hot press forging machine. The main parameters to be investigated are operation temperature (450C, 500C, 550C), holding time (1, 2 and 3 hours) and weight percentage (wt%) of rice husk (5, 10, 15 wt%) burnt at different temperatures. (700C, 900C and 1100C). The optimization of density will be done through the application of Design of Experiment (DOE) method by means of RSM. The AA6061 aluminium alloy as-received billet will be used as a reference for data comparison. Optimal results are obtained from ANOVA which parameters have the most significant effect to response of density. lower volume of fraction of RHA (<7%) and higher forging operation temperature (520-550C). Experiments with wider setting of parameters for forging process could be conducted.The research investigates about the rice husk reinforced aluminium chips by direct recycling. It is significant to study which will affect the physical and mechanical properties of composite. Due to increasing of natural wastes, rice husk is developed in an alternative method of recycling it as reinforcement for aluminium chips-based composite. Major purposes of this research are to investigate the physical property of directly recycled aluminium alloy AA6061 reinforced by rice husk via density test and simulate the effect of process parameters namely operation forging temperature, holding time, and weight percentage (wt%) of rice husk through DEFORM 3D software to reveal the optimum performance of the developed composite. The matrix composite used is recycled aluminium alloy AA6061 in chips with an average length of less than 4mm. The experiment is carried out by the hot press forging machine. The main parameters to be investigated are operation temperature (450C, 500C, 550C), holding time (1, 2 and 3 hours) and weight percentage (wt%) of rice husk (5, 10, 15 wt%) burnt at different temperatures. (700C, 900C and 1100C). The optimization of density will be done through the application of Design of Experiment (DOE) method by means of RSM. The AA6061 aluminium alloy as-received billet will be used as a reference for data comparison. Optimal results are obtained from ANOVA which parameters have the most significant effect to response of density. lower volume of fraction of RHA (<7%) and higher forging operation temperature (520-550C). Experiments with wider setting of parameters for forging process could be conducted.